New tools for precision livestock management - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
OTAG is a Specific Support Action implemented within the 6th Framework Programme of the EU commission. It may be used to help in preparations for future Community research and technological development policy activities including monitoring and assessment activities related to food safety and security